Association of income and education with fecundability in a North American preconception cohort - Schrager, Nina L. (Ann Epidemiol, 2020)
PURPOSE: To evaluate socioeconomic determinants of fecundability. METHODS: Among 8,654 female pregnancy planners from Pregnancy Study Online, a North American prospective cohort study (2013–2019), we examined associations between socioeconomic status and fecundability (the per-cycle probability of conception). Information on income and education was collected via baseline questionnaire. Bimonthly follow-up questionnaires were used to ascertain pregnancy status. We estimated fecundability ratios (FRs) and 95% confidence intervals (CI) using proportional probabilities regression, controlling for potential confounders. RESULTS: Relative to an annual household income of ≥$150,000, adjusted FRs were 0.91 (95% CI: 0.83–1.01) for <$50,000, 0.99 (95% CI: 0.92–1.07) for $50,000-$99,000, and 1.09 (95% CI: 1.01–1.18) for $100,000-$149,000. FRs for <12, 13–15, and 16 years of education, relative to ≥17 years, were 0.90 (95% CI: 0.76–1.08), 0.84 (95% CI: 0.78–0.91), and 0.89 (95% CI: 0.84–0.95), respectively. Slightly stronger associations for income and education were seen among older women. CONCLUSIONS: Lower levels of education and income were associated with modestly reduced fecundability. These results demonstrate the presence of socioeconomic disparities in fecundability.